A economia solidária e a promoção das liberdades instrumentais na perspectiva de desenvolvimento econômico de Amartya Sen - Magalhães, Luan Ferreira (2021)
The present work has as theme the Solidarity Economy, a form of transformative production that reflects on the relationship with income and economic development. In order to analyze how this type of initiative has the potential to promote the instrumental freedoms, from the perspective of economic development of Amartya Sen, it was intended to identify the profile of the enterprises of Solidary Economy in Brazil, according to the latest mapping published by SENAES, in 2014. The research was prepared from secondary data of the mapping of the enterprises of Solidarity Economy, published in 2014 by the SIES and also by bibliographic research, using books, academic articles and websites as sources. Based on the data collected it was possible to realize that the development process results in a series of processes that integrate and, subsequently, extend their effects when articulated. The realization of the instrumental freedoms in the enterprises of Solidary Economy replaced the current mode of production with a participatory management that valued the individuals. As shown throughout the work, the Solidarity Economy became a means for the economic agent to expand his freedoms and be a channel for promoting economic development.